Putusan PTUN No.193/G/LH/2015/PTUN-Jkt, Atas Pembatalan SK Gubernur DKI Jakarta No. 2238 Tahun 2014 Tentang Pemberian Izin Reklamasi Pulau G Kepada PT. Muara Wisesa Samudra - Raianny, Ayu; wibowo, Arif (LPPM Universitas Malikussaleh, 2024)
The reclamation of Island G in Jakarta Bay has sparked various controversies that eventually led to a lawsuit filed by Mr. Nelayan Muara Angke and several environmental groups against the Governor of DKI Jakarta and PT Muara Wisesa Samudra as the developer. Based on various considerations, the Jakarta Administrative Court (PTUN) decided to annul the Decree of the Governor of DKI Jakarta Number 2238 dated December 23, 2014, concerning the Implementation Permit for the Reclamation of Island G. One of the judges argued that the Governor of DKI Jakarta had the right to issue the reclamation permit for Island G, even though the authority to grant such permits formally belongs to the central government, as stipulated in Presidential Decree Number 52 of 1995 concerning the Reclamation of the Northern Coast of Jakarta, which has already expired. The revocation of the decree also created new legal consequences, particularly regarding the nullification of sale and purchase transactions that occurred prior to the revocation of the decree.